Neuroimaging Features of San Luis Valley Syndrome - Matthew T. Whitehead; Bonmyong Lee (Case Reports in Radiology)
A 14-month-old Hispanic female with a history of double-outlet right ventricle and developmental delay in the setting of recombinant chromosome 8 syndrome was referred for neurologic imaging. Brain MR revealed multiple abnormalities primarily affecting midline structures, including commissural dysgenesis, vermian and brainstem hypoplasia/dysplasia, an interhypothalamic adhesion, and an epidermoid between the frontal lobes that enlarged over time. Spine MR demonstrated hypoplastic C1 and C2 posterior elements, scoliosis, and a borderline low conus medullaris position. Presented herein is the first illustration of neuroimaging findings from a patient with San Luis Valley syndrome.